МУСИҚА МАДАНИЯТИ ДАРСЛАРИДА МУЛЬТИМЕДИЯ ВОСИТАЛАРИДАН ФОЙДАЛАНИШ - Пардаев, С. (SCIENCE and SOCIETY, 2018)
The article deals with the role of pedagogical technologies and multimedia means in increasing the effectiveness of the lesson.